Yountsville : The Rise and Decline of an Indiana Mill Town - Morris, Ronald V. (Book collections on Project MUSE., 2020)
"In Yountsville: The Rise and Decline of an Indiana Mill Town, Ronald Morris and collaborators examine the history and context of a rural Midwestern town, including family labor, working women, immigrants, and competing visions of the future. Combing perspectives from history, economics, and archeology, this exploration of a pioneering Midwestern company town highlights how interdisciplinary approaches can help recover forgotten communities. The Yount Woolen Mill was founded during the pioneer period by immigrants from Germany who employed workers from the surrounding area and from Great Britain who were seeking to start a life with their families. For three generations the mill prospered until it and its workers were faced with changing global trade and aging technology that could not keep pace with the rest of the world. Deindustrialization compelled some residents to use education to adapt, while others held on to their traditional skills and were forced to relocate. Educators in the county seat offered Yountsville the opportunity to change to an education-based economy. Both the educators and the tradesmen associated with the mill believed their chosen paths gave children the best opportunities for the future. Present-day communities working through industrialization and deindustrialization still push for educational reform to improve the lives of their children. In the Midwest, many stories exist about German immigrants working in urban areas, but there are few stories of immigrants as capitalists in rural areas. The story of the Yount family is one of an immigrant family who built an industry with talent, labor, and advantage. Unfortunately, deindustrialization, dislocation, adaptation, and reuse were familiar problems in the Midwest. Archeologists, scholars, and students of state and local history and the Midwest will find much of interest in this book"--